2004
DOI: 10.1001/archderm.140.8.925
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Sun Protection Between the First and Second Summers for Very Young Children

Abstract: Objectives: To determine if an intensive intervention directed to mothers of newborns would increase levels of sun protection practice and lower rates of sunburning for their children; and to examine changes in sun protection practices and burning rates experienced between the first and second summers of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Furthermore, studies of detailed and tailored education programs to mothers of young children (aged 6 and 18 months) have not shown sustained sunprotection practices. In one study, comprehensive sun protection began to decrease at a much earlier age than previously reported [38]. The findings from this study have brought to light a critical period when comprehensive sun protection starts to wane and skin damage in very young children begins to increase [38].…”
Section: Treatmentsupporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, studies of detailed and tailored education programs to mothers of young children (aged 6 and 18 months) have not shown sustained sunprotection practices. In one study, comprehensive sun protection began to decrease at a much earlier age than previously reported [38]. The findings from this study have brought to light a critical period when comprehensive sun protection starts to wane and skin damage in very young children begins to increase [38].…”
Section: Treatmentsupporting
confidence: 55%
“…The findings from this study have brought to light a critical period when comprehensive sun protection starts to wane and skin damage in very young children begins to increase [38]. Safe sun strategies should embrace multiple methods of sun protection, especially shading, and must be taught as part of routine preventive health care, in school settings, and likely emphasized again in preadolescent and adolescent years, when such sun protection habits are known to deteriorate [38,39]. Nevertheless, the future in sun protection may be brighter because one randomized controlled trial of a broad-spectrum SPF30 sunscreen in children showed that the sunscreen group developed fewer nevi, a surrogate endpoint for melanoma risk [40].…”
Section: Treatmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Unfortunately, studies have shown that increased knowledge, especially among adolescents and young adults, often fails to alter tanning behavior and attitudes. [12][13][14][15][16][17][18][19] It has been suggested anecdotally for years that one reason tanning is so popular is that UV light is addictive. [20][21][22] Many adolescents who regularly tan indoors self-report difficulty in quitting tanning.…”
mentioning
confidence: 99%
“…It is, however, reasonable to expect that skin-cancer prevention be discussed on at least a few visits during the course of a pediatrician's long-term relationship with a child and his or her family. Because parents' comprehensive sunprotection practices for children start to decline when children are very young, 230 it is important to begin discussions early in the child's life. Discussions are especially important for children at high risk of developing skin cancer-children with light skin, those with nevi and/or freckling, and those with a family history of melanoma.…”
Section: Discussionmentioning
confidence: 99%